Republic of Estonia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper examines developments in Estonia's expanding net external obligations, as well as in domestic income flows and balance sheets. The paper discusses external current account and net international investment positions. Domestic investment and saving and balance sheet developments for the domestic sectors are covered. The paper makes use of the IMF's new Global Econometric Model to investigate and quantify the role of market flexibility in Estonia. It also compares the results of simulations made under different assumptions about labor market and goods market flexibility.